Evaluation of Cytotoxic Activity of Lavandula stoechas Aerial Parts Fractions against HepG2 Cell Lines - Siddiqui, Mohd. A.; Siddiqui, Hefazat H.; Mishra, Anuradha; Usmani, Afreen (Current Bioactive Compounds, 2020)
Background: Lavandula stoechas is the main member of Labiatae (Lamiaceae) family. People use this medicinal plant in the treatment of several diseases around the world. The purpose of this work was to evaluate the cytotoxic effect of different fractions like ethanol, ethyl acetate and n-hexane from methanol extract of Lavandula stoechas aerial parts on HepG2 cell line and analysis of chemical composition of the most active fraction of the Lavandula stoechas aerial parts. Methods: Methanolic extract was prepared by cold maceration. Fractions from extract were prepared in solvents of increasing polarity i.e. n-hexane, ethyl acetate and ethanol. In order to evaluate the cytotoxic effect of Lavandula stoechas, MTT assay method was used. For this purpose, HepG2 cells line were treated with the above mentioned Lavandula stoechas aerial parts fractions with different concentrations 10, 25, 50, 100, 250, 500 and 1000 μg/ml. The cells without treatment were served as a control. Results: The result of this study showed that ethanolic fraction showed major reduction in % cell survival compared to other fractions. These results showed that Lavandula stoechas Ethanolic fraction was highly inhibitory. Further, phyto chemical analysis of ethanolic fraction was carried out using GC-MS technique and the reports showed Lupeol, Phytol, α-Cadinol, Lup-20(29)-en-3-one, hydrocoumarin, Lup-20(29)-en-3-one. Other compounds included fatty acids and their esters. Some of these compounds are being first time reported here from this plant. Conclusion: MTT assay showed morphological changes, which clearly support Lavandula stoecha ethanolic fraction possesses anticancer effect which may be due to the presence of phytosterols.
Keywords: MTT assay